Peran Digitalisasi dan Program Santripreneur melalui pendekatan SDGs dalam mewujudkan kemandirian Pondok pesantren (Studi Pada Ponpes Besar di Kab. Lamongan) - Sayyid, Mokhtar; Yeni Suyanto, Umar; Abadi, Muhammad Dzikri; Ni’mah, Jihan Lailatul; Cahyani, Rahma Indah (Politeknik Ganesha Medan, 2024)
The development of economic digitalization in Indonesia has increased quite significantly at this time. This has resulted in consumption patterns that were previously carried out by people physically, now shifting online. The business world is required to adapt to see the current phenomena. On the one hand, today's modern Islamic boarding schools are not only centers of studying religion, they also have great potential in the economy. They changed the paradigm in da'wah, which previously used verbally to change into action. So that it can be a solution to society's problems, which motivates Islamic boarding schools to try to combine the religious education system with entrepreneurial training known as santripreneur. This program is a breakthrough to realize the concept of sustainable development which has a good impact on human life and nature. This study aims to analyze the role of digitalization and the santripreneur program in realizing the independence of Islamic boarding schools when viewed based on the SDGs approach. The population in this study were Islamic boarding school students spread across Lamongan Regency. Sample selection was carried out using purposive sampling technique, with a sample of 353 respondents. Data analysis in this study used structural equation modeling partial least squares (SEM-PLS) techniques. The analysis results show that santripreneurs and digitalization have an influence on the SDGs. Santripreneurs have a direct effect on the economic independence of Islamic boarding schools, while digitalization does not directly affect the economic independence of Islamic boarding schools. SDGs are able to mediate the influence of santripreneurs and digitalization on the economic independence of Islamic boarding schools.